Penerapan Model Pembelajaran Kooperatif Jigsaw Mode Kamp untuk Meningkatkan Keterlibatan Siswa Dalam Pembelajaran PAI - Wasiatul Mahfidhoh Jaya Ningrum; Irma Soraya; Asep Saepul Hamdani (Kariman: Jurnal Pendidikan Keislaman, 2024)
The learning model has become a major focus in efforts to improve learning effectiveness, especially in Islamic Religious Education (PAI) subjects. One model that attracts attention is the Jigsaw Cooperative Model, which emphasizes inter-student collaboration to better understanding.  The study aims to explore the application of the Cooperative PAI Learning Model by reference to the Kemp steps. The research method uses a qualitative approach with relevant literature, including books, journals, articles, and other sources related to the chosen topic. The data collection method used is the search for information about various aspects or variables related to a research topic.  Research results show that the application of this model is able to improve student involvement in PAI learning, with more intensive and collaborative learning activities.  The findings underline the importance of implementing Kemp's measures in supporting the effectiveness of the PAI Cooperative Jigsaw Learning Model.  Teachers need to pay attention to planning, implementation, evaluation, and revision continuously to ensure optimal learning.  The practical implications of this research are to provide guidance for educators in adopting and implementing cooperative learning models that are oriented towards better learning outcomes in the context of PAI learning.